Assessment of the thermal behavior of lignins from softwood and hardwood species - Poletto, Matheus (Maderas. Ciencia y Tecnología, 2017)
The thermal behavior of lignins from softwood and hardwood species has been investigated using thermogravimetry and differential scanning calorimetry. Klason Lignin from Pinus taeda and Klason lignin from Eucalyptus grandis were studied. The differential scanning calorimetry results showed that both Klason lignins studied presented similar glass transition temperature. Thermogravimetric results showed that the lignin degradation occurs in three stages. The Klason lignin of Pinus taeda is more thermally stable than Eucalyptus grandis, probably because of the higher thermal stability of the guaiacyl units in softwood lignin. The degradation of both lignins initiate by a diffusion process. However when the conversion values are higher than 0,1 the lignin degradation mechanism is a complex procedure and involves the degradation of a highly condensed aromatic structure formed at the previous degradation stages.